Solvothermal Synthesis of M‐doped TiO2 Nanoparticles for Sonocatalysis of Methylene Blue and Methyl Orange (M = Cd, Ag, Fe, Ce, and Cu). Issue 6 (15th May 2017) - Naghibi, Sanaz; Gharagozlou, Mehrnaz
Abstract : M‐doped TiO2 nanoparticles were synthesized by a sol–gel‐assisted solvothermal method. X‐ray diffraction (XRD), transmission electron microscopy (TEM), and diffuse reflection spectroscopy (DRS) were used to characterize the as‐synthesized samples. The sonocatalytic performance of the specimens for methylene blue and methyl orange degradation was evaluated. XRD confirmed the formation of anatase as the unique phase in all samples. TEM showed that Cd, Cu, and Ce led to increased particle size in comparison to TiO2 nanoparticles, whereas Fe and Ag had no considerable influence on this parameter. DRS confirmed the change in the absorption edge, and E g values decreased in the range 4.6–1.2% by Cd, Ce, Fe, Cu, and Ag doping, respectively. Among the different dopants, only Cd and Ag improved the absorbance of UV–visible light, and only these samples induced sonodegradation of the dye models. It can be concluded that the improvement in the dye removal efficiency is not related to an increase in the crystallinity and/or a decrease in E g, but only related to the increase in absorbance. Abstract : M‐doped TiO2 nanoparticles (M = Cd, Ag, Fe, Ce, and Cu) were synthesized by the sol–gel‐assisted solvothermal method. All the samples contained anatase as a unique phase and had particle size <50 nm. Among different dopants, only Cd and Ag improved the absorbance of UV–visible light. Ag‐TiO2, and Cd‐TiO2 NPs induced sonodegradation of the dye models about 10 times greater than TiO2 ‐P25.